Pengaruh Sinkronisasi Pasokan Protein dan Energi Dalam Rumen pada Pakan Komplit Berbasis Bagase terhadap Produktivitas Domba - Novi Eka Wati (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2019)
The aim of the research was to study the effects of synchronization index in the sugarcane bagasse based complete feed on feed intake, daily body weight gain and feed conversion ratio of sheep. Two permanent cannulated male local sheep was 2 years old to create formulation of three diets with different synchronization index, namely 0.37; 0.50 and 0.63 respectively. Fifteen local male sheep with body weight average of 18,32 kg (cv= 14,39%) and aged at 12 months were feed a complete feed based on bagasse with a level of synchrony index 0,37; 0,50; 0,63 were design isoprotein and isoenergy. The treatments were allotted in a randomized block design with 3 treatments and 5 groups for in-vivo test. The feed intake, daily body weight gain and feed conversion ratio of fifteen rams were determined on week 8 of experimental period. The results of the study indicated that the synchrony index did not effect on feed intake, but daily body weight and feed conversion ratio was affected (P<0.05) by the treatment of synchrony index in diet. The daily body weight gain of P2 group was highest compared with P1 and P3 groups. The feed conversion ratio of P2 group was lowest compared with P1 and P3 groups. The alteration of the study indicated that the synchronization index level of 0.50 showed the best weight gain and feed conversion. Keywords: daily body weight, feed conversion ratio, feed intake, synchrony index